Edukasi Gizi Pencegahan Anemia Melalui Pengaturan Konsumsi Teh Pada Ibu Hamil Di Wilayah Kerja Puskesmas Kimi, Nabire - Diana Ode; Syarifah Adriana; Suci Oktaviani; Djulfa Rumagia (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Anemia in pregnancy remains a major public health problem in Indonesia, with a national prevalence of 27.7% based on the 2023 Indonesian Health Survey. In areas with limited iron-rich food access and a strong culture of daily tea consumption, the inhibitory effect of tannins and polyphenols on non-heme iron absorption further increases risk. This community service activity aimed to improve pregnant women's knowledge and awareness of anemia prevention through tea consumption management in the working area of Kimi Public Health Center, Nabire. Implementation was carried out on 8 December 2025 using interactive socialization, small-group discussion, a printed leaflet, and open-ended pre–post evaluation. Approximately 20 pregnant and lactating mothers participated. The activity was delivered by two lecturers and supported by two Nutrition Science students who distributed leaflets. Participants were able to answer open-ended questions on the definition, causes, and prevention of anemia, showed enthusiastic participation, and around 90% expressed a commitment to reduce excessive tea consumption. This activity contributed to strengthening community-based nutrition education and is recommended for periodic replication and integration with routine antenatal care services.